(untitled) (Research, Society and Development, 2019)
The lack of knowledge and influence of third parties often leads to the choice of saving materials that are often not safe, but it is up to the engineer to demonstrate the conditions to have a safe and economical structure. It presents first some types of slabs and their characteristics, immediately is exposed the definitions of the massive slab. Next, it is presented the calculation of this structure on the criteria and recommendations of NBR 6118: 2014: Concrete Structures Project - Procedure, incorporating basic concepts on the subject for the execution of the same. Four designs of slabs were adopted in order to carry out the study of this structure. Subsequently, the comparison of slab calculations with and without safety coefficients is performed. The objective of this work is to conclude the most advantageous structure, due to the comparative of the quantitative results of the structure where the advantages of a secure structure were analyzed.